Exploring bibliometric trends in augmented reality research for vocabulary enhancement - Mat Saud, Asmah; Mohd Ghalib, Mohd Feham; Abu Bakar, Radhwa (Diamond Scientific Publication, 2024)
The integration of Augmented Reality (AR) in educational contexts has become an increasingly prominent area of research, particularly in the domain of vocabulary enhancement. As AR applications in education grow, a gap emerges, necessitating a thorough bibliometric examination of the scholarly landscape dedicated to vocabulary enhancement. This study aims to fill this void by systematically exploring existing literature, identifying publication trends, collaborative networks, and emerging themes. Employing Scopus, we will conduct a systematic bibliometric analysis. The search will concentrate on articles related to AR and vocabulary enhancement. Using bibliometric software, we will extract and analyse data from 2003 to 2023, encompassing publication trends, citation patterns, co-authorship networks, and keyword analyses to discern the intellectual structure of the field. Collaborative networks and interdisciplinary trends will be elucidated, providing a nuanced understanding of the global research landscape. Keyword analysis will shed light on emerging themes and technological nuances within AR applications for vocabulary learning. This bibliometric exploration aspires to contribute a comprehensive understanding of the state of AR research in vocabulary enhancement. By mapping bibliometric patterns, the study intends to guide future research, inform educators and researchers about key trends, and foster interdisciplinary collaboration. The anticipated findings promise valuable insights into the intellectual fabric of AR-enhanced vocabulary learning, ultimately contributing to the advancement of educational technology and pedagogical practices